Iatrogenic Fistula Between the Aorta and the Right Ventricular Outflow Tract After Melody Valve Implantation: Case Report and Literature Review - Loureiro, P (2020)
We present the first case of an iatrogenic aorta to right ventricular outflow tract fistula after Melody valve implantation. A 11-year-old girl, born with tetralogy of Fallot with absent pulmonary valve, underwent surgical repair at three years old with a 15-mm homograft. At five years old, calcification and stenosis of the homograft prompted successful balloon angioplasty and five years later she underwent Melody valve implantation. During follow-up, she began to suffer fatigue on moderate exertion. Echocardiography, cardiac catheterization and computed tomography were performed and showed a significant fistula between the right coronary ostium and the right ventricular outflow tract proximal to the implanted valve. The patient underwent surgical repair and in long-term follow-up there is no evidence of the fistula. Iatrogenic fistula between the ascending aorta and the right ventricular outflow tract after percutaneous pulmonary valve implantation is an uncommon complication, and may grow over time. A high level of suspicion is required for this rare complication and a final aortography may be necessary for the diagnosis.